A new approach to predict the market and impacts of round-trip and point-to-point carsharing systems: case study of London - Le,Vine SE; Lee-Gosselin,MEH; Sivakumar,A; Polak,JW (Transportation Research Part D: Transport and Environment, 2014)
There are nearly two million subscribers to carsharing services worldwide. These services can provide large benefits both to users and the general public (e.g. through emissions reductions). There has not however previously existed a general framework for forecasting their market potential and impacts that is sensitive to the way that they re-structure the costs associated with personal car ownership. Techniques for predicting market scope and impacts ahead of field implementation are urgently required, both by entrepreneurs and the public sector, whose support, or at least acquiescence, is generally required.This paper draws on the Perceived Activity Set conceptual framework that was recently developed to address the methodological challenges posed by carsharing, and presents the first set of empirical findings from employing it to model carsharing. The empirical analysis makes uses of pooled data from the British National Travel Survey and a purpose-designed stated-choice survey. We investigate both the ‘round-trip’ and ‘point-to-point’ carsharing service models.The results suggest that the number of prospective subscribers to a point-to-point carsharing service in London is between three and four times as large as the comparable number for round-trip carsharing. The greatest reduction in overall vehicle-miles of travel – including both carsharing cars and private cars – was found from introducing round-trip carsharing across all of London. Survey respondents indicated they would use point-to-point carsharing for commuting journeys much more frequently than round-trip carsharing. Finally, point-to-point carsharing was found to be a substitute for public transport, whilst round-trip carsharing was found to be a complement.